Pollution characteristics, environmental issues, and green development of neonicotinoid insecticides in China: Insights from Imidacloprid - Wang, JinZe; Hou, Jie; Wang, LiXi; Zhu, ZiYang; Han, BingJun; Chen, LiYuan; Liu, WenXin (Environmental pollution (1987), 2025)
Imidacloprid (IMI), a leading neonicotinoid insecticide, is widely used in China. Nevertheless, owing to its high toxicity to pollinators, regulatory scrutiny of its usage has increased in recent years. Despite this, no relevant issues have been announced in China, and its usage continues to rise. In this study, we systematically reviewed the development history, pollution characteristics, and environmental problems associated with IMI in China, which is imperative to promote its green development. The results show that most IMI products (97.1%) in China are registered for agricultural use. Owing to its extensive use and strong migration ability in different environmental matrices, IMI has been broadly detected in multiple environmental media. The average detection rate (DR) of IMI in soils, ambient water, and sediments were 90.7%, 81.3% and 84.5%, respectively, and the corresponding concentrations were 54.6 ± 83.8 ng/g dry weight (dw), 32.8 ± 103 ng/L, and 1.7 ± 2.9 ng/g dw, respectively, indicating high IMI abundance in multiple environmental media in China. The spatiotemporal distribution of IMI was generally determined by its application modes, transport, and degradation rates. IMI is commonly overused in China, leading to the development of high IMI resistance in many pests, and a high DR of IMI in food, drinking water, and human bodies. To alleviate IMI pollution in China, the joint efforts of the government, farmers, and scientists are necessary, including but not limited to formulating laws and regulations, strengthening governmental supervision, improving farmers’ knowledge of IMI use, and promoting technological innovation in IMI and application methods. [Display omitted] •Imidacloprid (IMI) was broadly detected in multiple environment media in China.•Pesticide compounding and seed coating are common practices for new IMI products.•High residues in humans and increased insect resistance primarily limit IMI's further use.•Farmers, governments, and professionals should collaborate to reduce IMI pollution.